Development of high-throughput chemiluminescence imaging instrument for parallel evaluation of polymer lifetime. (November 2015) - Aratani, Naoki; Katada, Ikki; Nakayama, Koyuru; Terano, Minoru; Taniike, Toshiaki
Abstract: A high-throughput chemiluminescence imaging instrument is developed to realize facile and systematic data accumulation in degradation and stabilization of polymer. The instrument works based on imaging chemiluminescence of 100 oxidatively degrading polymer samples that are placed in a multi-cell with arrayed wells being flushed with atmospheric gas, and thereby enables simultaneous acquisition of 100 chemiluminescence curves. The present study reports validation and demonstrative application of the instrument for the oxidative degradation of stabilized polypropylene with a variety of hindered phenol anti-oxidants. Based on quantitatively accurate and large-volume data on oxidative induction time, not only the feasibility of the new instrument but also a number of useful aspects of stabilizers are demonstrated.